FAKTOR PENYEBAB TRANSMIGRAN BERTAHAN DI DESA ALUR KECAMATAN JORONG KABUPATEN TANAH LAUT - Reni Purwasih; Eva Alviawati; Ellyn Normelani (Universitas Lambung Mangkurat, 2016)
This research entitled “Factors Affecting Transmigrants Stay in Desa Alur Kecamatan Jorong Kabupaten Tanah Laut. The obejctive of this research is to know factors causing the transmigrants stayed in Desa Alur Kecamatan Jorong Kabupaten Tanah Laut.The population of this research is all householders who stayed in location of transmigration Desa Alur Kecamatan Jorong with the total number 383 householders. Technique of sampling of this research used proportional sampling with reference to the table Isacc and Michael. To determine the respondents used random sampling technique by means of a lottery. The method of this research is descriptive quantitative method. Technique of collecting data consists of primary and secondary techniques of collecting data. Primay data is gotten from observation and questionnaire. Secondary data is encountered from related departments such as Dinas Statistik, Dinas Tenaga Kerja and Transmigrasi, Kantor Camat Jorong and Kantor Kepala Desa Alur Kecamatan Jorong Kabupaten Tanah Laut. Data processing technique of this research used editing, scoring and tabulation techniques. Technique of Data Analysis used percentage technique.The result of the research shows that the factors affecting the transmigrants stayed in Desa Alur Kecamatan Jorong Kabupaten Tanah Laut is the experience in land cultivation an having fund, the complete facilities and infrastructured received in the location, the high work ethic, the raised of new innovation and technique, and the balance income owned by society.Keywords : Affecting Factors, Transmigrants Stayed